Pemulihan Kerusakan Jaringan Hati Mencit yang Diberi Ekstrak Butanol Buah Tua Mahkota Dewa - Soeksmanto, Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2007)
Mahkota dewa (Phaleria macrocarpa [Scheff.] Boerl.) is an Indonesians traditional medicinal plant used to treat various diseases, such as diabetes mellitus, hemorrhoid, impotency and cancer. Almost all parts of the plants canbe used as traditional medicine, but if directly consumed, it can cause swollen, sprue, numb at tongue, fever, even unconsciousness. This research was carried out to find out recovery of liver tissue damage of mice administered intraperitoneally with subchronic dosage of butanol extract 170 mg/kg body weight. Observation on first week showed that there is light degeneration (vacuolization) which is getting better on second week and apparentlynormal on forth week.